Novel variants in KAT6B spectrum of disorders expand our knowledge of clinical manifestations and molecular mechanisms. Issue 10 (14th September 2021) - Yabumoto, Megan; Kianmahd, Jessica; Singh, Meghna; Palafox, Maria F.; Wei, Angela; Elliott, Kathryn; Goodloe, Dana H.; Dean, S. Joy; Gooch, Catherine; Murray, Brianna K.; Swartz, Erin; Schrier Vergano, Samantha A.; et al.
Abstract: The phenotypic variability associated with pathogenic variants in Lysine Acetyltransferase 6B ( KAT6B, a.k.a. MORF, MYST4 ) results in several interrelated syndromes including Say‐Barber‐Biesecker‐Young‐Simpson Syndrome and Genitopatellar Syndrome. Here we present 20 new cases representing 10 novel KAT6B variants. These patients exhibit a range of clinical phenotypes including intellectual disability, mobility and language difficulties, craniofacial dysmorphology, and skeletal anomalies. Given the range of features previously described for KAT6B ‐related syndromes, we have identified additional phenotypes including concern for keratoconus, sensitivity to light or noise, recurring infections, and fractures in greater numbers than previously reported. We surveyed clinicians to qualitatively assess the ways families engage with genetic counselors upon diagnosis. We found that 56% (10/18) of individuals receive diagnoses before the age of 2 years (median age = 1.96 years), making it challenging to address future complications with limited accessible information and vast phenotypic severity. We used CRISPR to introduce truncating variants into the KAT6B gene in model cell lines and performed chromatin accessibility and transcriptome sequencing to identify key dysregulated pathways. This study expands the clinical spectrum and addresses the challenges to management and genetic counseling for patients with KAT6B ‐related disorders. Abstract : We describe 20 new cases harboring the KAT6B spectrum of disorders, which range from Say‐Barber‐Biesecker‐Young‐Simpson (SBBYSS) to Genitopatellar (GPS) syndrome or an intermediate phenotype. In our holistic approach, we expand the genotypic and phenotypic spectrum of KAT6B spectrum of disorders. Furthermore, we provide extensive clinical phenotyping, explore the impact of genetic counseling for these complex syndromes, and examine molecular mechanisms in RNA‐seq data in an in vitro cell model of truncating KAT6B mutations.